Factors Associated with Mortality of B-cell Non-Hodgkin Lymphoma Patients at Tertiary Care Hospital in Bali, Indonesia - Agustini, Made Priska Arya; Pratiwi, Made Sindy Astri; Yani, Made Violin Weda; Rena, Made Renny Anggreni (Indonesian Journal of Cancer, 2025)
Background: Non-Hodgkin Lymphoma (NHL) incidence has increased rapidly in recent decades. Although new treatment methods have been found, the mortality rate of NHL, especially in developing countries, is still high. Several factors can affect the mortality rate of NHL. However, data on factors related to the mortality rate of NHL patients in Bali are still not available. Therefore, this study aims to determine the survival rate and prognostic factors of mortality in NHL patients, especially those with the B-cell type, in Bali.Method: This study is a retrospective cohort study at Prof. I.G.N.G. Ngoerah General Hospital, Bali, Indonesia. The data was collected from electronic medical records from January 2020 to December 2023. The inclusion criteria for this study were all adult patients (aged ≥ 18 years) with a first-time diagnosis of B-cell NHL. Exclusion criteria included patients with other types of cancer, not undergoing chemotherapy, and incomplete medical records. Survival analysis and factors associated with mortality were analyzed using Kaplan-Meier curves, log-rank test, and Cox proportional hazards regression.Results: There were 143 B-cell NHL patients who met the inclusion criteria. The 1-year overall survival rate in this study was 59.4%, with a median survival time of 9 months. The majority of the causes of patient mortality were disease progression (76.7%). An ECOG Performance Status ≥2 (HR = 3.362; 95% CI 1.949 – 5.799; p = 0.000) and high-grade histopathological features (HR = 3.002; 95% CI 1.193 – 7.556; p = 0.020) were significantly associated with poor survival in B-cell NHL patients.Conclusion: The 1-year survival rate of B-cell NHL patients in Bali remains relatively low compared to previous studies. An ECOG performance status ≥ 2 and high-grade histopathological features are prognostic factors for mortality in B-cell NHL patients in Bali.